CYGNSS Satellite Sampling of Surface Heat Fluxes Across Atmospheric River Life Cycles - Shakeel Asharaf; Bin Guan; Duane E. Waliser (Geophysical Research Letters)
Abstract This study employs CYGNSS data to explore the life cycle of atmospheric rivers (ARs) on a near global scale, focusing on ocean surface turbulent heat flux variations. Using spaceborne measurements matched to different stages of full AR life cycles for the first time, we show declining latent and sensible heat fluxes throughout the AR life cycle, with the latent heat flux dominating. The observed reduction in heat fluxes, despite increasing wind speed, suggests that temperature and humidity vertical gradients are the primary drivers of these changes during the AR life cycle. The decreasing temperature and humidity gradients indicate rapid declines in air temperature and humidity levels relative to the ocean surface. Our findings suggest the potential role of air‐sea interactions in driving moisture transport from the tropics to higher latitudes within ARs, and offer a satellite‐based benchmark for improving model fidelity in representing air‐sea processes during ARs.